Development of controller for fast plasma position control coils with ISO-FLUX scheme on JT-60SA. (23rd September 2022) - Kojima, S; Inoue, S; Miyata, Y; Urano, H; Suzuki, T
Abstract: Two types of poloidal magnetic field coils, superconducting poloidal field (SCPF) coils and in-vessel coils called fast plasma position control (FPPC) coils, will be installed in JT-60SA. We presented the different roles of SCPF and FPPC coils. The SCPF coils control plasma position and shape (P/S) and plasma current ( I p ), whereas the FPPC coils stabilize the perturbation of the n = 0 mode of magnetohydrodynamic (MHD) instability, such as vertical instability. This study developed a controller that outputs a coil voltage command for the power supply connected to each coil based on an ISO-FLUX scheme using an equilibrium control simulation code, MHD equilibrium control simulator (MECS). This controller stabilizes the horizontal and vertical plasma displacements using FPPC coils. FPPC coils have the advantage of FPPC due to fast coil current response; however, the induced current is also driven in FPPC coils. Thus, we proposed a control logic to mitigate the induced currents, particularly when the induced voltage is large. The difference in coil current response for SCPF and FPPC coils causes the coupling problem. Thus, decoupling between the SCPF and FPPC coils was established by employing the derivative treatment on the ISO-FLUX scheme in the FPPC control. To investigate the effectiveness of the FPPC control, using MECS we evaluated the allowable I p disruption intensity, which causes the plasma horizontal displacement, in the high elongation plasma, which relates to the plasma vertical displacement. Higher I p disruption intensity and elongation were allowed by adding the FPPC control. We investigated the controllability in the plasma ramp-up and flat-top operations. The support of FPPC control for SCPF control expands the plasma operation region which contributes to achieving the planned plasma operation in JT-60SA.